2017
DOI: 10.1371/journal.pone.0186048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weekend admission on mortality associated with severe acute kidney injury in England: A propensity score matched, population-based study

Abstract: BackgroundIncreased in-hospital mortality associated with weekend admission has been reported for many acute conditions, but no study has investigated “weekend effect” for acute kidney injury requiring dialysis (AKI-D).MethodsIn this large, propensity score matched cohort of AKI-D, we examined the impact of weekend admission and in-centre nephrology services in 53,170 AKI-D admissions between 1st April 2003 and 31st March 2015 using a hospital episode statistic dataset. Propensity score matching (PSM) was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous studies suggested a reduction in medical staffing and resources as well as a possible restriction in diagnostic and therapeutic tools on weekends to be responsible for the observed differences in mortality and morbidity [ 2 , 3 ]. While studies have shown a weekend effect for different medical conditions (including acute kidney injury [ 4 ], pneumonia [ 5 ] or dysrhythmia [ 6 ]) major commonalities among conditions affected by a weekend effect are the need for time sensitive interventions and care at an intensive care unit. In line with this, there are numerous reports about a weekend effect for stroke [ 7 9 ] myocardial infarction [ 10 , 11 ] or pulmonary embolism [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested a reduction in medical staffing and resources as well as a possible restriction in diagnostic and therapeutic tools on weekends to be responsible for the observed differences in mortality and morbidity [ 2 , 3 ]. While studies have shown a weekend effect for different medical conditions (including acute kidney injury [ 4 ], pneumonia [ 5 ] or dysrhythmia [ 6 ]) major commonalities among conditions affected by a weekend effect are the need for time sensitive interventions and care at an intensive care unit. In line with this, there are numerous reports about a weekend effect for stroke [ 7 9 ] myocardial infarction [ 10 , 11 ] or pulmonary embolism [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kolhe et al conducted a study on more than 53,000 dialysis-dependent AKI patients. The prevalence of WE admission was 23%, and WE admissions were significantly associated with higher mortality in the unadjusted model, but not in the multivariable analysis [ 26 ]. Finally, Holmes et al did not find any WE effect for mortality associated with hospital-acquired AKI [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest a number of factors that might account for increased mortality and morbidity rates during weekends, including a reduction in medical staff, limited resources, and restricted access to diagnostic and therapeutic tools [ 6 , 7 ]. Some studies have demonstrated unfavourable outcomes of the weekend effect on certain medical conditions such as pneumonia [ 8 ], acute kidney injury [ 9 ], and dysrhythmia [ 10 ]; favourable outcomes for these medical conditions rely on time-sensitive interventions and admission to intensive-care units. The findings of these studies have generated a significant degree of discussion on the validity of the weekend effect and its relationship to reduction in-hospital staffing practices for weekend shifts, a bias toward disease severity, and comorbidities associated with patients seeking hospital care during the weekend [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%